PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP MOTIVASI DAN KINERJA KARYAWAN DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN (DPRKP) DAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (DPUPR) KABUPATEN SUMBAWA - Alwan Patawari; Aryana Satrya; Jaka Warsihna (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this study is to analyze the effect of the work environment, career development, work motivation on employee performance. The research object and population in this study were employees of the Public Housing and Settlement Area Office (DPRKP) and the Public Works and Spatial Planning Office (DPUPR) of Sumbawa Regency. The number of samples is 200 people who work at the Public Housing and Settlement Area Office (DPRKP) and the Public Works and Spatial Planning Office (DPUPR) of Sumbawa Regency. The data analysis technique used is path analysis. Based on the results of the classical assumption test, it was found that the model met the required assumptions. The results of hypothesis testing show that 1) the work environment has a positive and significant effect on employee performance at the Public Housing and Settlement Area Office and the Public Works and Spatial Planning Office of Sumbawa Regency; 2) The work environment has a positive but not significant effect on the Work Motivation of employees of the Public Housing and Settlement Area Office and the Public Works and Spatial Planning Office of Sumbawa Regency; 3) Career Development has a negative but not significant effect on the Employee Performance of the Public Housing and Settlement Area Office and the Public Works and Spatial Planning Office of Sumbawa Regency; 4) Career Development has a positive and significant effect on the Work Motivation of the Public Housing and Residential Area Office Employees and the Public Works and Spatial Planning Office of Sumbawa Regency; 5) Work Motivation has a positive and significant effect on Employee Performance at the Public Housing and Settlement Area Office and the Public Works and Spatial Planning Office of Sumbawa Regency.